Efficacy of Complementary Therapies in the Quality of Life of Breast Cancer Survivors - Zaidi, Sahar; Hussain, Showket; Verma, Shalini; Veqar, Zubia; Khan, Asiya; Nazir, Sheeraz Un; Singh, Neha; Moiz, Jamal Ali; Tanwar, Pranay; Srivastava, Anurag; Rath, G. K.; Mehrotra, Ravi (Frontiers in Oncology, 2018)
Abstract Breast cancer is the most common cancer diagnosed in women and the second most common cancer overall, ranking as the fifth cause of death from cancer. The chronicity of the disease produces long-term physiological and psychological manifestations, which adversely affect the quality of life of the individual. The primary treatment while managing cancer presents with various debilitating side effects. With the recent advances in treatment techniques that have improved the survival rate, patients suffer from continuing post-treatment complications. Patients seem to cope well with the stress of treatment of breast cancer and sustain a normal life; however, the deterioration in physical well-being makes the patient functionally inefficient. Exercise has been proven to be an effective, safe and feasible tool in combating the adverse effects of treatment, prevent complications and decrease the risk of BC-specific mortality. This review briefly presents an overview of the burden of the disease and its management strategies. Owing to the heterogeneity of the population and the multitude of therapies they receive, the response of each patient to treatment is different and so is the magnitude of adverse effects. The review discusses the late sequelae following treatment and evidence supporting the role of physical activity in their management. In conclusion, there is a need for personalized physical activity plans to be developed to suit the individual and their circumstances.